DAMPAK KESEHATAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Dio Prananda; Idris Idris; Dewi Zaini Putri (Universitas Negeri Padang, 2018)
This study aims to determine and analyze the impact of life expentacy, fertilitiy rates, morbidity rates, and investment on economic growth in Indonesia. This type of research is associative descriptive research, where the data used was secondary data from 1985 to 2015 obtained from related institutions, which are analyzed using the Ordinary Least Square (OLS) method. The findings of this study indicate that life expectancy, fertility rates, morbidity rates, and investment have a significant effect on economic growth in Indonesia. Keywords: life expectancy, fertility rates, morbidity rates, investment, and Ordinary Least Square (OLS)